OPTICALLY STIMULATED LUMINESCENCE DATING OF THE UPPER HORIZON OF A SERBIAN LOESS-PALEOSOIL SEQUENCE USING QUARTZ - AVRAM, Anca; MANDROC, Marius; CONSTANTIN, Daniela; MARKOVIĆ, Slobodan; TIMAR-GABOR, Alida (Studia Universitatis Babeș-Bolyai Ambientum, 2021)
Optically stimulated luminescence dating is widely used for establishing high-resolution chronologies for the Quaternary in paleoclimate research. Loess is an important archive of past climate changes on continents. In order to provide a first absolute chronology for Zemun loess paleosol sequence in Serbia, the single-aliquot-regenerative dose (SAR) protocol was applied on coarse (63-90 µm) quartz fraction extracted from five samples. The profile reaches a thickness of 4 m, where the modern soil is visible in the uppermost part of the section. The investigated samples were collected from the transition between the uppermost visible soil and the loess layer, based on field observations. The results of the SAR-OSL protocol intrinsic rigor tests indicate that it can be successfully applied on coarse quartz extracted from Zemun samples, as all the results were within accepted limits of variation. The equivalent doses determined range from 14 ± 2 Gy (ZMN 55A) to 21 ± 2 Gy (ZMN 75A). Thus, the luminescence ages obtained for the investigated samples vary between 5.4 ± 0.7 ka (ZMN 55A) and 9.3 ± 1.2 ka (ZMN 75A). According to the ages obtained all the samples are assigned to the Holocene period.